PENGARUH BIMBINGAN TEKNIK MENYIKAT GIGI TERHADAP STATUS KEBERSIHAN GIGI DAN MULUT ANAK TUNAGRAHITA - Eldarita, Eldarita; Amanullah, Rizqi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Dental health education is used as a measuring tool to generate knowledge and awareness that can influence a person's attitudes and habits towards oral and dental hygiene. Low oral health knowledge can be affected to children's attitudes and actions. The study aims to determine the effect of guidance on the technique of brushing teeth on the oral hygiene status of mentally retarded children, the output of this study is expected to be useful as a reference in improving the ability of brushing techniques and oral and dental hygiene. The research design was quasy experimental design with a pre test and post test with control group approach. The study was conducted at SLB Wiyata Dharma 4 Godean Sleman in October 2019. Data analysis using t-test statistical tests. The results showed that there was an increase in knowledge, abilities and status of dental and oral hygiene of mentally retarded children. Statistical test results obtained p value = 0.00 The conclusion of the study was that there was a significant influence between the guidance of brushing teeth on the oral and dental hygiene status of mentally retarded children. It is recommended that mentally retarded children increase awareness and apply brushing knowledge in maintaining oral and dental hygiene.